Medical Conditions and Oral Diseases in Elderly Thai Dental Patients in Lower Northern Thailand - Kaomongkolgit, Ruchadaporn; Daroonpan, Pissacha; Tantanapornkul, Weeraya; Palasuk, Jadesada; Chansamat, Ronnayut (Journal of Dentistry Indonesia, 2019)
The World Health Organization (WHO) aims to strengthen oral health promotion and disease prevention around the globe. The prevalence and association of systemic diseases and oral diseases has been reported. Objectives: The objectives of this study were to investigate prevalence of medical conditions and oral diseases in elderly Thai dental patients. Methods: Three hundred dental records of patient aged 60 years old and older were retrospectively reviewed. Data were analyzed using Pearson’s Chi-square and Fisher›s exact test with the significant level at p < 0.05. Results: All of them were Thai of 142 males (47.3%) and 158 females (52.7%). Their age ranged between 60 and 85 years old with an average age of 66.1 ± 5.4 years old. Two third of patients had the history of systemic diseases (66.3%) and hypertension (10.3%) was the predominant one. Eighty-nine percent of patients had oral health problems. Fifteen percent were currently on antiplatelet and anticoagulant drugs, and 15.4% had the history of drug allergy. The most prevalent oral diseases were tooth loss (87.7%) followed by periodontal diseases (80.0%), tooth wear (66.0%), dental caries (65.3%) and pulp diseases (54.0%). The prevalence of oral mucosal lesions, temporomandibular disorder and orofacial pain were 23.7%, 1.6% and 1.6%, respectively. Conclusion: The present study provides the information of medical conditions and oral diseases in a group of older Thai dental patients in the lower northern Thailand.